Prognostic Factors for Sudden Drops in Hearing Level After Minor Head Injury in Patients With an Enlarged Vestibular Aqueduct. Issue 1 (January 2015) - Noordman, Bo Jan; van Beeck Calkoen, Eveline; Witte, Birgit; Goverts, Theo; Hensen, Erik; Merkus, Paul
<x xml:space="preserve">Abstract</x> Objective To identify factors associated with sudden drops in hearing level after minor head trauma in patients with an enlarged vestibular aqueduct (EVA). Methods A systematic review of the literature on sudden drops in hearing level after minor head trauma in patients with an EVA was conducted. The studies were retrieved from Embase, PubMed, CINAHL, and Cochrane and critically appraised using predefined criteria. Data on all described parameters were collected, and their relation with sudden drops after minor head trauma was statistically analyzed. Results Pooled data of 31 articles included 179 patients with 351 EVAs. Drops in hearing level after minor head trauma were experienced by 34% of the patients. We found a significant association between sudden deterioration of hearing after minor head trauma and preexisting fluctuating hearing loss (HL) (odds ratio, 8.6; p < 0.001; 95% confidence interval, 3.9–19.3). The diameter of the VA, type of preexisting HL, severity of HL, preexisting progressive HL, and the diagnosis Pendred syndrome were not significantly associated with sudden drops in hearing levels after head trauma. Conclusion Only one-third of the patients with a proven EVA experienced sudden drops in hearing level because of head trauma. There is a significant association between preexisting fluctuating HL and the chance of sudden drops in hearing level caused by trauma. Stringent lifestyle advices, like avoiding activities with a risk of minor head trauma such as contact sports, might be restricted to patients with a fluctuating HL and those with a history of sudden drops on minor head trauma.